Maternity Care Provider Views on Disrespect, Mistreatment, and Obstetric Violence in Australian Maternity Services - Emma C. Collins; Elaine S. Burns; Hazel Keedle; Hannah G. Dahlen (Journal of Advanced Nursing, 2026)
ABSTRACT Background Around one in ten Australian women describe feeling powerless, violated and dehumanised during the perinatal period resulting in physical and psychological trauma. Maternity care providers are also impacted when mistreatment of women is undertaken or witnessed. Aim To explore the perspectives and experiences of maternity care providers (midwives, doctors and doulas) regarding disrespect, mistreatment and obstetric violence in Australian maternity services. Methods A qualitative study was undertaken using a constructivist/subjectivist paradigm underpinned by Critical Feminist Theory. Data were collected through in‐depth semi‐structured interviews conducted October 2024 to January 2025 and analysed thematically. Findings There were four main themes identified including: ‘disrespect and mistreatment in Australian maternity services’, ‘the normalisation of disrespect and mistreatment’, ‘obstetric violence is a polarising term’ and ‘wide reaching impacts of disrespect and mistreatment for women and maternity care providers’. Discussion Study participants described witnessing and involvement in instances of disrespect, mistreatment and obstetric violence recognising that both individuals and organisational systems and structures contribute to its occurrence. Using the lens of Critical Feminist Theory, the discussion explores three key areas: everyone is hurt by the occurrence of disrespect and mistreatment, the term obstetric violence is polarising, and the need to address systems and structures that enable disrespect, mistreatment, and obstetric violence rather than focusing on individuals. Conclusions Collaborative systemic improvements are necessary within Australian maternity services to foster respectful maternity care through legislative and policy improvements, and education at both the individual and system‐wide level. No Patient or Public Contribution Patients and members of the public did not contribute to study design, conduct or reporting. Midwives, doctors and doulas participated in the study in their professional roles. The research team included experienced midwives in an academic research capacity rather than as patient or public contributors.